ANHYPOSTATOS-ENHYPOSTATOS: CHURCH FATHERS, PROTESTANT ORTHODOXY AND KARL BARTH - Lang, U. M. (1998)
U. M. LANG; ANHYPOSTATOS-ENHYPOSTATOS: CHURCH FATHERS, PROTESTANT ORTHODOXY AND KARL BARTH, The Journal of Theological Studies, Volume 49, Issue 2, 1 October 19